The Zebrafish Meiotic Cohesin Complex Protein Smc1b Is Required for Key Events in Meiotic Prophase I - Islam, Kazi Nazrul; Modi, Maitri Mitesh; Siegfried, Kellee Renee (Frontiers in Cell and Developmental Biology, 2021)
The eukaryotic structural maintenance of chromosomes (SMC) proteins are involved in key processes of chromosome structure and dynamics. SMC1b was identified as a component of the meiotic cohesion complex in vertebrates, which aids in keeping sister chromatids together prior to segregation in meiosis II and is involved in association of homologous chromosomes in meiosis I. The role of SMC1b in meiosis has primarily been studied in mice, where mutant male and female mice are infertile due to germ cell arrest at pachytene and metaphase II stages, respectively. Here, we investigate the function of zebrafish Smc1b to understand the role of this protein more broadly in vertebrates. We found that zebrafish smc1b is necessary for fertility and has important roles in meiosis, yet has no other apparent roles in development. Therefore, smc1b functions primarily in meiosis in both fish and mammals. In zebrafish, we showed that smc1b mutant spermatocytes initiated telomere clustering in leptotene, but failed to complete this process and progress into zygotene. Furthermore, mutant spermatocytes displayed a complete failure of homolog pairing and synapsis. Interestingly, meiotic DNA double strand breaks occurred in the absence of Smc1b despite failed pairing and synapsis. Overall, our findings point to an essential role of Smc1b in the leptotene to zygotene transition during zebrafish spermatogenesis. In addition, ovarian follicles failed to form in smc1b mutants, suggesting an essential role in female meiosis as well. Our results indicate that there are some key differences in Smc1b requirement in meiosis among vertebrates: while Smc1b is not required for homologue pairing and synapsis in mice, it is essential for these processes in zebrafish.